One transition story does not fit them all: Initial regional conditions and new business formation after socialism - Michael Fritsch; Maria Kristalova; Michael Wyrwich (Friedrich Schiller University Jena, 2020)
We investigate the reasons for the pronounced regional differences of new business formation after the transformation from a socialist planned system to a market economy in East Germany. Relatively high start-up rates are found in regions that had a well-qualified workforce and a relatively high share of remaining self-employed at the end of the socialist period. This also holds for high-tech manufacturing start-ups. Based on our conclusion that policy should account for these initial regional conditions, we use two criteria to introduce a classification of regions.
Keywords: L26; R11; N94; P25; 330; Entrepreneurship; new business formation; regional conditions; transformation; East Germany